Analisis Risiko Kejadian Kecelakaan Kerja Pada Petani Tambak di salah satu Pos UKK Kalitengah Kabupaten Lamongan - Ratnasari, Ardiana Vita; Cahyani, Merditha Tri (Universitas Ivet, 2021)
The highest number of work accidents in Indonesia in 2011 – 2014 was in 2013 that is 35.917 cases of work accidents (2011 – 9.891; 2012 = 21.735; 2014 = 24.910). The objective of this research is to analyze the factors related to the risks of work accidents of the fish farmers in the Work Health Efforts. The qualitative approach with study plan of cross sectional was used in this research with samples of this research are similar to the number of population that is 100 people. The data analyses used in this research were univariate, bivariate with chi square, and multi-variant with logistic regression of backward method. The results showed that 56% of fishermen had high risk of work accidents. The factor related to the risks of work accidents are education (p=0,037) and the factors that are not related to the risks of work accidents are habit (p=0,361) and knowledge (p=0,916). The factor that has the stronger influences towards the risks of work accidents is an unsafe condition (p=0,0001). The recommendation of this research is the need of continuous training on the work accident prevention for the fishermen in accordance with their educational background and knowledge.